Hyperhomocysteinemia as an Early Predictor of Erectile Dysfunction: International Index of Erectile Function (IIEF) and Penile Doppler Ultrasound Correlation With Plasma Levels of Homocysteine. Issue 39 (September 2015) - Giovannone, Riccardo; Busetto, Gian Maria; Antonini, Gabriele; De Cobelli, Ottavio; Ferro, Matteo; Tricarico, Stefano; Del Giudice, Francesco; Ragonesi, Giulia; Conti, Simon L.; Lucarelli, Giuseppe; Gentile, Vincenzo; De Berardinis, Ettore
Abstract : Abstract: Erectile dysfunction (ED) is inability to achieve and maintain an erection to permit satisfactory sexual activity. Homocysteine (Hcys) is a sulfur-containing amino acid synthesized from the essential amino acid methionine. Experimental models have elucidated the role of hyperhomocysteinemia (HHcys) as a strong and independent predictor for atherosclerosis progression and impaired cavernosal perfusion. The aim of this study is to investigate the serum levels of Hcys in our cohort of patients with ED, to compare these values with these of control population and to examine Hcys as a predictive marker for those patients who are beginning to complain mild–moderate ED. A total of 431 patients were enrolled in the study. The whole cohort was asked to complete the International Index of Erectile Function (IIEF) questionnaire. The study population was divided in 3 main groups: Group A: 145 patients with no ED serving as a control group; Group B: 145 patients with mild or mild–moderate ED; Group C: 141 patients with moderate or severe ED. Each participant underwent blood analysis. All patients underwent baseline and dynamic penile Doppler ultrasonography. We found in our cohort mean Hcys plasma concentrations significantly higher than the cut-off point in both groups B and C (18.6 ± 4.7 and 28.38 ± 7.8, respectively). Mean IIEF score was 27.9 ± 1.39, 19.5 ± 2.6, and 11.1 ± 2.5 for groups A, B, and C, respectively ( P  < 0.0001). In the penile Doppler ultrasonography studies, a high significant inverse correlation was detected between the mean values of the 10th minute's peak-systolic velocity (PSV) and Hcys levels for the groups B and C. This establishes a dose-dependent association between Hcys and ED. Furthermore, we showed that Hcys was an earlier predictor of ED than Doppler studies, as the Hcys increase was present in patients with mild ED even before abnormal Doppler values.